D’vocca Chocolate Sdn. Bhd. / Eliza Mohd. Razak... [et al.] - Mohd. Razak, Eliza; Hashim, Noor Azura; A.Aziz, Zafizul Aida; Che Wan, Nur Azleena; Sudin, Suriati (2001)
D'Vocca Chocolate Sdn Bhd is the name of our company. We decided to choose manufacturing product based on chocolate as our business. It is because the business has a good potential to growth in the country because the demand of the consumer for this product is high. It's market size also large. Our chocolate product has various shapes and flavor. The business location is situated at Mergong Barrage 2 area and its strategic place because it situated in an industrial area. So, we would like to take a chance to open our factory over there. The location is near with the highway and city. It is also near with main road and housing area. We choose this business because easy to get raw material in the market. We are going to commerce our business starting on January 2003.